Patients‘ Nursing Needs After Intestinal Stoma Forming Surgery - Kuklytė, Rūta; Paulikienė, Simona (Slauga. Mokslas ir praktika, 2020)
This article analyzes the patient nursing needs after the bowel formation surgery. The study included 28 nurses from the surgical department and 4 patients (three of them had ileostomas, one colostomy). The questionnaire survey and interview methods were used for the research. Patients with post-traumatic formation surgery need more nursing and hygiene vital nursing needs than after colostomy formation. In addition, these patients need more knowledge about parastomy care. After the colostomy formation operation, the more urgent nutritional needs of eating and drinking are influenced by the influence of eating on the time of the release. Also, these patients have more psychological problems and more need for communication due to physical body changes.